Special operations forces medical handbook - Farr, Warner D. (Skyhorse Publishing, 2011)
A resource of useful medical information created for Special Forces medics and soldiers shows the proper techniques for medical care, from basic first-aid and orthopedics to instructions for emergency war surgery and veterinary medicine.